2020
DOI: 10.1016/j.redox.2020.101659
|View full text |Cite
|
Sign up to set email alerts
|

SERCA overexpression reduces reperfusion-mediated cardiac microvascular damage through inhibition of the calcium/MCU/mPTP/necroptosis signaling pathways

Abstract: Endothelial cells lining the microvasculature are particularly vulnerable to the deleterious effects of cardiac ischemia/reperfusion (I/R) injury, a susceptibility that is partially mediated by dysregulated intracellular calcium signals. Sarco/endoplasmic reticulum Ca 2+ -ATPase (SERCA) functions to recycle calcium from the cytosol back to the endoplasmic reticulum. The purpose of this study is to explore the roles and mechanisms of SERCA in protecting microcirculation against cardiac I/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 76 publications
1
33
0
Order By: Relevance
“…The activity and expression of SERCA are essential for maintaining a baseline calcium release or resting intracellular calcium. Various studies have reported the cardioprotective effects of SERCA [ 12 , 34 , 35 ]. The decreased expression of SERCA can mediate endothelial cell necrosis in ischemia-reperfusion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The activity and expression of SERCA are essential for maintaining a baseline calcium release or resting intracellular calcium. Various studies have reported the cardioprotective effects of SERCA [ 12 , 34 , 35 ]. The decreased expression of SERCA can mediate endothelial cell necrosis in ischemia-reperfusion.…”
Section: Discussionmentioning
confidence: 99%
“…As the main site of ROS production and the first target of ROS attack, excessive ROS production can lead to dysfunction of mitochondrial respiratory electron-transport chain and further affect the balance of redox in cells [ 10 ]. Therefore, under the stimulation of hypoxia, inflammation, and high glucose, it will lead to excessive production of ROS and induce structural and functional abnormalities of mitochondria, including imbalance of mitochondrial energy metabolism, reduction of mitochondrial biosynthesis, and abnormal opening of mitochondrial membrane permeability transition pore (mPTP) [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Reactive Oxygen Species (ROS) Assays. ROS were measured after staining with dihydroethidium (DHE; Invitrogen, USA) [31]. The fluorescence was observed under microscopes and further analysed by flow cytometry.…”
Section: Isolation Of Cardiomyocytes and Primary Cell Culture Inmentioning
confidence: 99%
“…It was confirmed that both concentrations of ethanol downregulated key genes related with calcium signaling pathway (Figure 6). Interestingly, previous studies also found that dysfunction in calcium signaling is involved in endothelial dysfunction (Cheriyan et al, 2020; Li et al, 2020; Wang et al, 2020). Key genes related with PI3K‐Akt signaling pathway were also downregulated by ethanol, but 50‐mM ethanol appeared to be more effectively compared with 5‐mM ethanol (Figure 7).…”
Section: Discussionmentioning
confidence: 94%